Throughout, $A$ and $B$ denote $n \times n$ matrices over $\mathbb{C}$. Everyone knows that the determinant is multiplicative, and the trace is additive (actually linear). \begin{align*} \det(AB) = \det(A)\det(B) && \mathrm{tr}(A+B)= \mathrm{tr}(A) + \mathrm{tr}(B). \end{align*} On the other hand, the opposite equations \begin{align} \det(A+B) = \det(A)+\det(B) && \mathrm{tr}(AB)= \mathrm{tr}(A)\mathrm{tr}(B) \tag{1}. \end{align} don't hold for all $A,B$ unless $n=1$. For instance, taking $A=B=I$ in (1), we get \begin{align*} \det(A+B) = 2^n && \det(A)+\det(B) = 2 && \mathrm{tr}(AB)= n && \mathrm{tr}(A)\mathrm{tr}(B) = n^2. \end{align*} When $n=2$ a very curious thing happens, which is that, even though the equations (1) are typically false, their sum is actually valid. That is, \begin{align} \det(A+B) + \mathrm{tr}(AB)= \det(A)+\det(B)+ \mathrm{tr}(A)\mathrm{tr}(B) \tag{2} \end{align} for all $A$ and $B$ when $n=2$. However, (2) does not hold when $n>2$. Indeed, specializing to $B=I$ in (2), we get \begin{align} \det(A+I) + \mathrm{tr}(A)= \det(A)+1+ n \cdot \mathrm{tr}(A) \end{align} or, equivalently, \begin{align} \det(A+I) = \det(A)+(n-1) \cdot \mathrm{tr}(A) +1 \tag{3}. \end{align} If $n \geq 2$ and $A$ is projection onto the first coordinate, we have \begin{align} \det(A+I) = 2 && \det(A)+(n-1)\cdot \mathrm{tr}(A) +1 = n, \end{align} so (3) is only an identity for $n=2$ (or, trivially, when $n=1$).

Question: Is there any special significance to the equation \begin{align} \det(A+B) + \mathrm{tr}(AB)= \det(A)+\det(B)+ \mathrm{tr}(A)\mathrm{tr}(B) , \end{align} which is valid for all $2 \times 2$ matrices? It seems very strange to me that the sum of two obviously false equations should turn out true. Are there any nice applications of this identity?

  • $\begingroup$ Woah! This is such a crazy observation. (In a good way.) $\endgroup$ – goblin GONE Oct 20 '15 at 22:46

In a quite pedestrian way, this is just saying that $\det$ is a quadratic form with the trace as its polar form. Namely, for any matrix $A$, let $A^\star = \mathrm{Tr} A - A$ be its conjugate (as in “the conjugate root of the characteristic polynomial”). Then your formula is equivalent to $$ \det (A+B) - \det(A) - \det(B) = \mathrm{Tr}(A^\star \cdot B).$$ The left-hand side is the polar form associated to the determinant form.

In a slightly more abstract way, for any field $k$, the matrix algebra $k^{2\times 2}$ is a (split) quaternion algebra. The formula above is just the polar relation for the norm form in this algebra (which is the determinant of a matrix).

| cite | improve this answer | |
  • $\begingroup$ Thanks for the reply! I'm not sure I'm following, however. So, if I define $b(A,B) = Tr(A^\star B)$, then I get a bilinear form $b$ on the vector space of $2 \times 2$ matrices. It's even symmetric: $b(A,B) = Tr(A)Tr(B) - Tr(AB) = Tr(B)Tr(A) - Tr(BA) = b(B,A)$. OK, so that means it should satisfy a polarization identity: $b(A,B) = \frac{1}{2}\left( q(A) + q(B) - q(A-B) \right)$ where $q(X) = b(X,X)$ is the associated quadratic form. You are claiming the associated quadratic form is basically the determinant. However, I get $b(A,A) = Tr(A)^2 - Tr(A^2)$? What am I missing? $\endgroup$ – Mike F May 5 '15 at 7:26
  • $\begingroup$ OK never mind, I see. $Tr(A)^2 - Tr(A^2) = 2 \det(A)$ for $A$ 2-by-2. Which is pretty bizzare in and of itself... Thanks! $\endgroup$ – Mike F May 5 '15 at 7:34
  • $\begingroup$ This last fact is a simple consequence of the characteristic polynomial $A^2 - t A + d = 0$ - taking traces gives $$\mathrm{Tr} (A^2) - t \mathrm{Tr} (A) + \mathrm{Tr} (d) = 0,$$ or $$\mathrm{Tr} (A^2) - t^2 + 2d = 0.$$ $\endgroup$ – Circonflexe May 5 '15 at 10:05
  • 2
    $\begingroup$ That's a neat trick. So, trying the same thing for the $n=3$ case, I can use that $A$ satisfies its own characteristic polynomial: $A^3 + s_2(A) A^2 + Tr(A) A - \det(A) I = 0$, where $s_2(A)$ is defined to be the quadratic coefficient of the characteristic polynomial, and then take the trace to get $Tr(A^3) + s_2(A) Tr(A^2) + Tr(A)^2 - 3\det(A) = 0$ which shows that $\det(A) = \frac{1}{3} ( Tr(A^3) + s_2(A) Tr(A^2) + Tr(A)^2)$ $\endgroup$ – Mike F May 5 '15 at 16:41
  • $\begingroup$ The $n=2$ formula $\det(A) = Tr(A^2) - Tr(A)^2$ is a bit more intriguing to me, though, since it seems to suggest $\det(A)$ is something like the "variance" of the matrix a la the formula $Var(X) = E(X^2) - E(X)^2$. Certainly it is reasonable to think of the trace as some kind of expectation functional, being as how $\frac{1}{n} Tr(A)$ is the average of the spectrum. $\endgroup$ – Mike F May 5 '15 at 16:44

This is the case $n=2$ of a 1980 theorem of Amitsur. It is described (in more abstract notation) here and this question gives the reference to Amitsur's paper.

| cite | improve this answer | |
  • 1
    $\begingroup$ Thanks, that's nice to know! So, for instance, when $n=3$ we have the formula $\det(A+B) = \det(A)+\det(B) + s_2(A) \mathrm{tr}(B) + \mathrm{tr}(A) s_2(B) $ $- (\mathrm{tr}(A) + \mathrm{tr}(B)) \mathrm{tr}(AB) + \mathrm{tr}(A^2B + BAB)$ where $s_2(X)$ denotes the 2nd coefficient of the characteristic polynomial of $X$. I guess that last term could also be written as $\mathrm{tr}(A^2B) + \mathrm{tr}(AB^2)$. $\endgroup$ – Mike F May 5 '15 at 7:06
  • 4
    $\begingroup$ It would be be nice if you could quote the actual formula. $\endgroup$ – nbubis May 5 '15 at 15:39
  • $\begingroup$ @MikeF - Why does your formula true?.Please guide me. $\endgroup$ – H.... Feb 6 '16 at 0:04
  • $\begingroup$ See my separate answer where I confirm this formula. Note the sign of the $s_2$ terms above assumes the convention $|x\mathbf 1-A|$ for the characteristic polynomial. $\endgroup$ – Colin MacLaurin Dec 26 '19 at 9:25

@MikeF gives a further formula for $n=3$, under the answer by @Flounderer. (I would have made this answer just a comment there, but it's a bit too long.) The formula comes from de Smit apparently, as linked in that answer. See de Smit's line starting "$s_3(x+y) = \cdots$". I checked the formula using brute force in Mathematica. Note my added minus sign with the $s_2$ terms, because of the convention $|A-\mathbf 1x|$ for the characteristic polynomial: A = {{a11, a12, a13}, {a21, a22, a23}, {a31, a32, a33}} B = {{b11, b12, b13}, {b21, b22, b23}, {b31, b32, b33}} s2A = Coefficient[CharacteristicPolynomial[A, x], x] s2B = Coefficient[CharacteristicPolynomial[B, x], x] Simplify[ Det[A + B] == Det[A] + Det[B] - (s2A Tr[B] + Tr[A] s2B) - (Tr[A] + Tr[B]) Tr[A.B] + Tr[A.A.B] + Tr[A.B.B] ]

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.